(untitled) (Swiss Medical Weekly, 2023)
INTRODUCTION: Hair-thread strangulation syndrome describes the constriction of a body part by a tightly wound hair or thread. This research aims to review the literature about this entity. METHODS: A systematic review was performed to characterise hair-thread strangulation syndrome in subjects aged ≤16 years. This pre-registered review (PROSPERO ID: CRD42022363996) followed the PRISMA methodology. RESULTS: Subjects with digital strangulation were significantly younger (median = 4.0 [interquartile range: 2.0–6.1] months; n = 143) than females with genital strangulation (9.0 [6.8–11] years; n = 36), males with genital strangulation (5.1 [1.9–8.0] years; n = 36), and subjects with non-digital and non-genital strangulation (24 [13–48] months; n = 11). Digital strangulation was followed by an amputation in five (3.5%) and a reconstructive surgical intervention in seven (4.9%) cases. Sequelae occurred in four (11%) cases after female genital strangulation: clitoris autoamputation (n = 2) and surgical removal of a necrotic labium minus (n = 2). Severe complications were observed in 14 (39%) cases with male genital strangulation: urethral fistula (n = 7), urethral transection (n = 2), and partial penile autoamputation (n = 5). A partial uvular autoamputation was observed in one case (9.0%) with non-digital and non-genital strangulation. CONCLUSIONS: Early recognition and management are crucial to avoid sequelae or long-term care in hair-thread strangulation syndrome.